True Government by Choice Men? Inspection, Education, and State Formation in Canada West; Colonial Leviathan: State Formation in Mid-Nineteenth Century Canada - Palmer, Bryan D. (Labour / Le Travail, 1993)
The article reviews the books, "True Government by Choice Men? Inspection, Education, and State Formation in Canada West," by Bruce Curtis, and "Colonial Leviathan: State Formation in Mid-Nineteenth Century Canada," edited by Allan Greer and Ian Radforth.
Keywords: BOOKS -- Reviews; COLONIAL Leviathan: State Formation in Mid-Nineteenth-Century Canada (Book); CURTIS, Bruce; GREER, Allan; Nonfiction; RADFORTH, Ian; TRUE Government by Choice Men? Inspection, Education & State Formation in Canada West (Book)